Investigating The Students’ Awareness Of Speaking Skills In Efl Classroom - Hasanah, Uswatun; Pratiwi, Dwiyani (CV. Inara, 2024)
Self-awareness is a crucial aspect for students that can boost their learning motivation and contribute to success. The purposes of this research are to find out the types of self-awareness of speaking ability the students use in the EFL classroom and to identify strategies implemented to solve the students' awareness problems of speaking skills in the classroom. This study is descriptive qualitative research. The participants were nine students from one of the state Universities in Yogyakarta. The data collection instruments were an observation sheet and interview guidelines. Furthermore, the researcher used thematic analysis to analyze the data. Triangulation was also used to assess the credibility of the data. The results showed that students continue to embrace advice even when it is met with adverse feedback or comments. A subset of students believes that embracing recommendations from their peers will facilitate their future development. By cultivating precise self-awareness, students can enhance their ability to identify errors and effectively use available technologies to enhance their pronunciation and vocabulary. Thus, in the future, when they desire to engage in oral communication, they will undergo enhancement. Furthermore, certain students dared to stand up and present themselves before the entire class while frequently experiencing feelings of anxiety and fatigue. However, certain individuals require further training to enhance their confidence and fluency in addressing the class. Minor behaviors enhance students' self-assurance, influencing their emotional state and averting a deterioration in confidence. Classroom speaking presents many problems for students. Even when they have problems with speaking skills, students try to use ways to improve. Students use YouTube and learning apps to view more native-language videos and improve their speaking skills. These help with speaking pronunciation.